Adsorption of asphaltenes on mixed oxide synthesized by auto-combustion method. Issue 8 (3rd August 2019) - González, Máximo Oliva; Kharisov, Boris I.; Quezada, Thelma Serrano; Kharissova, Oxana V.; Hernández, Lucy González; de la Fuente, Idalia Gómez
Abstract: The oil classified as heavy is the one with the largest number of deposits at present. However, these deposits are usually difficult to exploit since they contain a high concentration of asphaltenes which cause problems in the refineries at the time of extraction. Different strategies were used to decrease the effects of asphaltenes, being the most effective the use of adsorbents based on metal oxides. This is because metal oxides prevent the re-precipitation of asphaltenes under oil extraction; these methods can be easy implemented in modern refineries. In this work, we propose the synthesis of mixed oxide (Ni(3/2) x Fe2- x O4 ) by self-combustion technique, being then used as an effective asphaltene adsorbent. Its asphaltene adsorption capacity was compared with nickel oxide and hematite, which were synthesized by controlled precipitation. The oxides were characterized by the techniques of X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR); their morphological characterization was carried out by scanning electron microscopy (SEM). The capacity of adsorption of asphaltenes was determined with the technique of UV-Vis spectroscopy. The results show that the Ni(3/2) x Fe2- x O4 is a good adsorbent being compared with hematite and nickel oxide, both for asphaltenes with ether and amino groups. The mixed oxide shows a mayor affinity to asphaltenes containing amino groups, being compared with the hematite and nickel oxide; in addition, the mixed oxide has a low affinity to petroleum, which makes it selective to asphaltenes. Graphical Abstract: